2015
DOI: 10.1007/s00420-015-1094-2
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of small aids during patient handling activities lead to a decreased occurrence of musculoskeletal complaints and diseases? A systematic review

Abstract: CRD42014009767.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
0
21
2
Order By: Relevance
“…Several of these studies investigate and credit the ceiling-lift [25,27,[42][43][44], which we presently show to elicit the lowest biomechanical load among the included assistive devices. However, these results somewhat contrast the findings of systematic reviews, showing that manual handling training by itself does not lower the risk of musculoskeletal injuries [21,45].…”
Section: Risk Of Back Injury and Lbpcontrasting
confidence: 95%
“…Several of these studies investigate and credit the ceiling-lift [25,27,[42][43][44], which we presently show to elicit the lowest biomechanical load among the included assistive devices. However, these results somewhat contrast the findings of systematic reviews, showing that manual handling training by itself does not lower the risk of musculoskeletal injuries [21,45].…”
Section: Risk Of Back Injury and Lbpcontrasting
confidence: 95%
“…Freiberg et al [ 30 ] examined the effectiveness of using small (non-technical) aids (e.g., sliding sheets and walking belts) during patient handling and their impact on the occurrence of musculoskeletal complaints with a systematic review, and found the current level of evidence for their preventive use to be inadequate. While evidence for the preventive use of small aids is deficient, until now the evidence from interventions with technical aids has not yet been considered in a systematic review.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 12 SRs reported on different interventions for the prevention of musculoskeletal disorders. They included mixed interventions with several different components,21–25 physical exercises at the workplace,26 work organisation and psychosocial working environment,27 educational interventions for the prevention of musculoskeletal disorders,28 ergonomic interventions29 and interventions in the area of manual handling of loads 30–32…”
Section: Resultsmentioning
confidence: 99%
“…Aids for patient transfer (both small aids such as bed steps, anti-slip mats, etc, and mechanical aids such as mechanical transport devices for patients) led to positive effects on pain and/or injuries of the musculoskeletal system in two SRs (QoE: very low to low) 30 31. Stock et al 27 showed that ‘lifting programmes’ as well as multi-component interventions on safe patient handling in hospitals had no effect on several outcomes measured (eg, the prevalence of neck/shoulder pain, forearm/wrist pain, lower back pain and musculoskeletal pain in any body region; upper extremity or back-related functional status; musculoskeletal work injury rates and time loss injury rates; QoE: very low to low) except for two outcomes: they found low-quality evidence that a safe lifting programme is more effective than usual practice in reducing the frequency of work-related shoulder pain and work-related low back pain (QoE: low) 27…”
Section: Resultsmentioning
confidence: 99%